Dampak Penggunaan Digital Banking dan Kepuasan Nasabah serta Implikasinya Terhadap Tingkat Tabungan - Letlora, Ingrid Julia; Metekohy, Stellamaris; Pattilouw, Djufri Rays (Public Policy, 2024)
Public interest in using digital banking is increasing every month so banks need to maintain and increase customer satisfaction because that is also the main factor in increasing the use of digital banking applications. Digital banking is a banking service that facilitates customers to carry out all their financial activities via smartphone, from opening an account to electronic banking. Electronic banking, also called e-banking, is provided by banks to fulfill important services in carrying out banking transactions. This research aims to find out how digital banking influences the savings rate at PT. Bank Rakyat Indonesia (Persero) Tbk, Masohi Branch Office, Central Maluku Regency. The data analysis method uses path analysis (Path Analysis). The results of this research show that there is a direct influence between digital banking on customer satisfaction and it is significantly positive, there is a positive influence between customer satisfaction and increasing the amount of savings. Meanwhile, the indirect influence of digital banking on the amount of savings through customer satisfaction is also positive and significant